1978
DOI: 10.1111/j.1365-2389.1978.tb02051.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Potassium Reserves Available to Plant Roots

Abstract: Successive extraction with Ca-saturated sulphonated resin is used to remove potassium from soils. The kinetics of K-release are analysed mathematically to define three simultaneous rate processes by the amounts and rate-functions associated with them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

1981
1981
2004
2004

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 4 publications
0
35
0
1
Order By: Relevance
“…Potassium release kinetics evaluated through sequential Ca-resin extraction show that only "surface" and "periphery" K as defined by Talibudeen et al (1978) are differentiated by fertilization regimes. Long-term K supply capacities are not modified by the treat-ments; KO and K4 soils had similar release rate coefficients for slow K release from the clay matrix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potassium release kinetics evaluated through sequential Ca-resin extraction show that only "surface" and "periphery" K as defined by Talibudeen et al (1978) are differentiated by fertilization regimes. Long-term K supply capacities are not modified by the treat-ments; KO and K4 soils had similar release rate coefficients for slow K release from the clay matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology developed by Talibudeen et al (1978) was applied to the soil of the KO and K4 plots from block III. Experimentally, 2 g of calciumsaturated Amberlite IR-120 resin (Serva, 20-50 mesh, 2.3 meq g-l) was placed in a centrifuge tube with 10 ml of deionized water and 1 g of soil was added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surapaneni et al (1991), however, showed that the nitric acid method was superior to the NaTPB method for yellow-grey earth soils. Alternative methods of measuring the exchangeable and non-exchangeable K-releasing power separately are mainly based on exchange processes in soils e.g., exchange isotherms (Goulding 1983(Goulding , 1986Elkhatib & Hern 1988), quantity and intensity (Q/I) relationships (Beckett 1964;Lee 1973;During & Duganzich 1979;Sparks & Huang 1985;Haby et al 1990;Cervantes & Hanson 1991;Herlihy 1992), electro-ultrafiltration (Nemeth 1982;Sparks 1987;Haby et al 1990;Liu et al 1992;Herlihy 1992), and cation exchange resins (Lee & Gibson 1974;Talibudeen et al 1978;Martin & Sparks 1985). These methods are not used in New Zealand and, according to Sparks (1987), are of little practical value for predicting K-releasing power.…”
Section: Methods Of Assessing Exchangeable Plus Non-exchangeable K-rementioning
confidence: 99%
“…This differs from the sequence that occurs through the cation reaction using sodium tetraphenylboron (NaTPB) . Few studies have been conducted on the kinetics of nonexchangeable K release from whole soils (Talibudeen and Weir, 1972;Talibudeen et al, 1978;Martin and Sparks, 1983;Sadusky and Sparks, 1985). Martin and Sparks (1983) investigated the kinetics of nonexchangeable K release from two coastal plain soils from Delaware using an H-resin ( Figure 11).…”
Section: Specific Studiesmentioning
confidence: 98%